2022
DOI: 10.3390/brainsci12091187
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Structural Differences and Prediction of Autistic Traits during Adolescence

Abstract: Background: Autistic traits are commonly viewed as dimensional in nature, and as continuously distributed in the general population. In this respect, the identification of predictive values of markers such as subtle autism-related alterations in brain morphology for parameter values of autistic traits could increase our understanding of this dimensional occasion. However, currently, very little is known about how these traits correspond to alterations in brain morphology in typically developing individuals, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Research has confirmed that limbic regions such as the amygdala and hippocampus are functionally related to impaired abilities in ASD, which are correlated with repetitive and stereotyped behavior (Fu et al, 2022 ; Nees et al, 2022 ; Thabault et al, 2022 ). Our results showed that the limbic gray value in the ASD group was lower than that in the adult HC group.…”
Section: Discussionmentioning
confidence: 97%
“…Research has confirmed that limbic regions such as the amygdala and hippocampus are functionally related to impaired abilities in ASD, which are correlated with repetitive and stereotyped behavior (Fu et al, 2022 ; Nees et al, 2022 ; Thabault et al, 2022 ). Our results showed that the limbic gray value in the ASD group was lower than that in the adult HC group.…”
Section: Discussionmentioning
confidence: 97%
“…In other words, autistic traits have a robust correspondence with reduced brain volume in the hippocampus that is related to social processing, working memory, perceptual reasoning, and spatial learning. One possible hypothesis is that high-functioning autistic populations may experience an adaptive reduction in hippocampal volume as a result of their decreased specific functional demands on the hippocampus and altered interactions with the environment ( 37 ). Decreased hippocampal volume in ASD individuals was also related to impaired language skills, including verbal learning and memory ( 32 , 38 ).…”
Section: Hippocampal Involvement In Individuals With Asdmentioning
confidence: 99%
“…Moreover, our planned "high-altitude" training of autistic children and their parents in our hypoxia chamber will commence in due course (L. P. with H. E.). This is a worldwide unique pilot study in a frequent condition, challenging diagnostic competences as well as reliability of follow-up measures, 133,134 and thus far lacking biology-based treatments. 135 We hypothesize that intensive motor-cognitive training within a defined social setting (family condition) that consists of 3 h daily for 3 weeks in a hypoxia training chamber (12% O 2 ; conditions comparable as described above for adults) will lastingly improve autistic symptoms and motor performance as well as improve cognitive dysfunction in children diagnosed with autism and/or intellectual disability.…”
Section: Pilot Study On Motor-cognitive Training Under Inspiratory Hy...mentioning
confidence: 99%